Evaluation of Pedagogical Content Knowledge (PCK) in the Readiness of Biology Education Students as Prospective Educators - Prasetyo, Mohammad Mulyadi; Taskirah, Andi; Nurhidayah, Nurhidayah (Jurnal Pendidikan Biologi, 2023)
Knowledge about how to present material so that it is easier to understand is called PCK (Pedagogical Content knowledge). PCK needs to be owned by teaching staff or prospective teaching staff to determine the approach or method used in delivering learning material so that it is more effective and meaningful. Apart from that, PCK is also one of the standards in preparing teaching staff. The aim of this research is to evaluate PCK in the readiness of biology education students to become prospective teaching staff. This research uses descriptive methods and is quantitative research. The research subjects were nine biology education students. Samples were taken using purposive sampling. PCK data is collected using a questionnaire while data on teaching ability is taken through assessment sheets. Data were analyzed descriptively with percentages and categorized based on score interpretation criteria. The results of this research show that PCK is included in the good category with a percentage of 77.72% and basic teaching abilities are also included in the good category with a percentage of 78.92%. Teachers who have good PCK are able to prepare learning optimally. Teaching ability is also the key to the success of the teaching and learning process, because students gain a lot of experience during the learning process. The conclusion from the results of this research is that the overall PCK of biology education students is included in the good category, which proves that they have the preparation to become educators.